HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL DENGAN KUNJUNGAN ANTENATAL CARE (ANC) DI WILAYAH KERJA PUSKESMAS GLUMPANG BARO KABUPATEN PIDIE - Muliati Muliati; Salmiani Abdul Manaf; Yuni Sari; Yushida Yushida; Fitriani Fitriani (PT. Intelek Cendikiawan Nusantara, 2025)
Efforts to accelerate the reduction of maternal mortality rate (MMR) are carried out by ensuring that every mother has access to quality healthcare services. These services include antenatal care, delivery assistance by trained health personnel at healthcare facilities, postnatal care, specialized care and referrals in the event of complications, and family planning services. According to data from Glumpang Baro Health Center in 2023, the number of targeted pregnant women was 254, with 137 (54%) attending the first antenatal visit (K1), and only 139 (55.0%) completing the fourth visit (K4), which is significantly below the 95% target set by the Ministry of Health. ANC visit attendance is influenced by factors such as the level of knowledge and attitudes of pregnant women.